PENERAPAN METODE PEMBELAJARAN KONTRUKTIVISTIK UNTUK MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA SMP - Sariasih, Ni Made (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
This research was classified as action research. It took 27 students studying in class VIII in the even semester of the Academic Year 2021/2022 at SMP Negeri 2 Selemadeg. This classroom action research aimed to improve the Indonesian language learning achievement of class VIII B students of SMP Negeri 2 Selemadeg in the academic year 2021/2022 by using the Constructivistic learning method and it was tried out in implementing the learning process. The belief that emerged from the beginning was that the use of the traditional models used by the teachers to teach everyday was an obstacle to the expected learning achievement so that the researcher chose a more constructive model. After the data was collected by using the learning achievement test and analyzed by using the descriptive analysis, it was gained the increase of the students’ achievement from the initial pre-cycle data 62.22 then in cycle I with the average value increased to 69.81 and in cycle II it increased again to 81.11. The increase that occurred was quite significant from pre-cycle, cycle I, and cycle II. Thus, the action hypothesis "The implementation of the Constructivistic Method can Improve the Indonesian Language Learning Achievement for class VIII B students of SMP Negeri 2 Selemadeg in the academic year 2021/2022 " could be accepted because there had been a significant increase in the learning achievement. The conclusion drawn was that the constructivist learning methods could improve the students’ learning achievement.